Optimalisasi Web Desa Guna Penyampaian Informasi Perkembangan dan Kegiatan Desa - Ruth Ema Febrita; Muhammad Fuad Al Haris; Eka Mistiko Rini; Mohammad Hisam (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The village website is one of the infrastructures that must be provided by the local government to convey information related to village development, village potentials, and their activities to the society. However, most village websites in Rogojampi District have a very minimal frequency of updating information. This community service aims to equip village officials with the skills to present data digitally so that information updating activities can be improved. This activity is carried out in three stages, which are preparation, workshop, and evaluation - mentoring. At the preparation stage, coordination with partners is carried out to map the initial skills of prospective participants and the material to be provided. At the workshop stage, participants are equipped with the skills to design infographics using Canva and the application of Search Engine Optimization (SEO) techniques on websites. Participants are accompanied for one month to update information on the village website. As many as 90% of village officials who participated in the training have updated the information on their website. Thus the service activities have been successful